AUDITING OF TRAFFIC SIGNS AND ROAD MARKINGS IN DAR ES SALAAM CITY - Bwire, Hannibal; Mnkeni, Joseph K (Tanzania Journal of Engineering and Technology, 2017)
This study examines the efficacy of the traffic signs and road markings in Dar es Salaam City. The study focuses on the availability and conditions of traffic signs and road markings in some selected roads in the city. Auditing of traffic signs and road markings is carried out as one of the means of promoting road safety and improving road capacity in the city. The auditing procedure involved field studies through the use of traffic signs/markings checklists and ranking of road stretches according to the availability and conditions of traffic signs observed for improvement prioritization in case of financial constraints. In ranking the road sections in accordance to the overall conditions and availability of traffic signs, an index was developed. The index considered six factors of traffic signs availability and conditions that were observed in the field; (i) availability (ii) correctness of size (iii) visibility of signs (iv) physical condition (v) correct placement and (vi) the need of sign protection. It is recommended that the responsible agency and Municipal councils carry out auditing of traffic signs/markings independently and identify deficiencies in signage and road markings and plan for improvement accordingly. In case of financial constraints, the developed performance index may be used to rank roads/road sections for improvement priority.